Post-Demonetization E-Payment Trends - Nirupam Bajpai; John Biberman; Jeffrey Sachs (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2018)
Developing a solid foundation for electronic payment systems is an integral part of ICTdriven development for any country. Compared to cash, e-payment transactions offer the advantages of portability, security, and convenience. For interpersonal transactions, epayments enable instantaneous exchanges of funds without requiring large sums of physical currency to be carried around and exchanged. E-payments also allow money to be sent rapidly to any recipient regardless of location, eliminating the time cost of making transactions over distance. Integrated e-payment systems are vital to the functioning of any ICT platform whose services require payment, especially those based on mobile technology. Finally, e-payments are more visible than cash transactions, reducing the corrupting influence of black money, widening the tax base, improving data on spending and consumption, and aiding in the formalization of large sectors of the economy. India has long been a cash-based economy, but in recent years, the country has been in the process of transitioning towards a cashless society, In November 2016, this transition was accelerated when 87% of the country's paper currency by value was demonetized. The macroeconomic merits of demonetization remain up for debate, but the policy shock did provide India a golden opportunity to replace legacy systems with ones that could interface with new IT platforms and the country's national ID database, Aadhaar. Although digital payment remains relatively infrequent for now, total digital payments are expected to reach USD 500 billion by 2020, ten times the level in 2016. Government has encouraged this transition by linking public transactions such as Direct Benefit Transfer (DBT) to e-payment services through Aadhaar. (...)
Keywords: 330; demonetization; UPI; Aadhar; formal economy; digitization; Digital Villages